2019
DOI: 10.18632/oncotarget.27024
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific membrane antigen expression in hepatocellular carcinoma: potential use for prognosis and diagnostic imaging

Abstract: Aim The prostate-specific membrane antigen (PSMA) is currently being established as a potent diagnostic marker in many tumor types. So far, its evidence in hepatocellular carcinoma (HCC) is sparse. The aim of our study was a comprehensive evaluation of PSMA expression and its prognostic role in patients with hepatocellular carcinoma as well as feasibility test of PSMA as an agent for diagnostic imaging. Methods The cohort for immunohistochemistry consisted of 153 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 16 publications
3
29
0
Order By: Relevance
“…A previously published limited immunohistochemistry study showed that 74–80% of HCC tumors presented moderate-to-strong staining for PSMA, while completely negative staining was seen in only 4–26% of samples [ 11 , 19 ]. All studies showed PSMA expression in the neovascular structures [ 11 , 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previously published limited immunohistochemistry study showed that 74–80% of HCC tumors presented moderate-to-strong staining for PSMA, while completely negative staining was seen in only 4–26% of samples [ 11 , 19 ]. All studies showed PSMA expression in the neovascular structures [ 11 , 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previously published limited immunohistochemistry study showed that 74–80% of HCC tumors presented moderate-to-strong staining for PSMA, while completely negative staining was seen in only 4–26% of samples [ 11 , 19 ]. All studies showed PSMA expression in the neovascular structures [ 11 , 12 , 19 ]. Tolkach et al [ 19 ] also reported PSMA expression on the canalicular membrane within the liver, but no expression was detected in the vasculature of the surrounding normal liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of HCC shows high levels of PSMA expression on tumor vessels and on canalicular membrane of cells [26,28] and therefore important implications for PSMAtargeted imaging and therapy arise. PSMA-targeted imaging of HCC in clinical practice has been evaluated only by a few studies and most of these studies are case reports [22,23,[27][28][29][30][31][32][33][34], probably because of the small number of centers that currently use radiolabelled PSMA PET/CT or PET/ MRI, resulting in a reduction of the population of patients overall studied.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 55 articles were extrapolated with the computer literature search and by reviewing the titles and abstracts 43 of them were excluded because the reported data were not within the field of interest of this review. Twelve articles were selected and retrieved in full-text version [22][23][24][25][26][27][28][29][30][31][32][33]; one additional study was found screening the references of these articles [34]. A total of 13 articles were then included in the systematic review [22][23][24][25][26][27][28][29][30][31][32][33][34] (Fig.…”
Section: Literature Searchmentioning
confidence: 99%
“…From the cancerous cells, it is primarily expressed in benign and malignant prostatic tissue [ 192 ]. However, studies on the PSMA-expression in also other tumor types are available, including breast, gastric, and colorectal cancer, lung and renal carcinoma, and brain tumors [ 193 , 194 , 195 , 196 , 197 , 198 ]. Thus, PSMA has become one of the most promising and extensively evaluated molecular targets in nuclear medicine.…”
Section: Onco-receptors and Their Target-specific Radiometal Labelmentioning
confidence: 99%